Tatwir Wasiilat at-Ta'lim 'ala Asas Smart Apps Creator biraasm Spline 'ala Mada as-Saa'a fi at-Ta'lim al-Lughah al-'Arabiyyah li-Talabat as-Saf ath-Thaamin fi al-Madrasah ath-Thaaniyyah Buwa, Luwu - Tosimpak, Hasanuddin; Pamessangi, Andi Arif; Chaeril, Chaeril (Al Ibrah: Journal of Arabic Language Education, 2024)
AbstractThis research discusses the development of a teaching method based on Smart Apps Creator using Spline drawing for the Arabic language subject for eighth-grade students in Buwa, Luwu High School. The aim of this research is describing the procedures for developing the teaching method using Smart Apps Creator with Spline drawing for the Arabic language subject for eighth-grade students in Buwa Luwu High School, and determine the validity of the teaching method with the application of Smart Apps Creator. The research design employed in this study is the research and development model proposed by ADDIE, which includes Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at Buway Lawoo High School, focusing on eighth-grade students and the Arabic language subject. To assess the validity of the developed product, a validity test was conducted by the subject matter expert and the instructional media expert. To determine the practical application of the product, practical application questionnaires were distributed to the students. The results of this research indicate that the teaching method using Smart Apps Creator with Spline drawing is highly valid and effective for teaching the subject material, as evaluated by the subject matter expert (92% very valid), the instructional media expert (76% very valid), the subject school expert (89% very valid), and the students (91% very valid).Key words: Development, method, Smart Apps Creator, Spline drawing????????? ??? ????? ?? ????? ????? ??????? ??? ???? Smart Apps Creator ???? Spline ??? ???? ?????? ?? ??????? ????? ??????? ????? ???? ?????? ?? ??????? ???????? ???? ????. ???? ??? ????? ??? 1) ??? ??????? ????? ????? ??????? ???????? Smart apps creator ???? Spline ??? ???? ?????? ?? ??????? ????? ??????? ????? ???? ?????? ?? ??????? ???????? ???? ????. 2) ????? ??? ??? ????? ?????? ????? ??????? ?? ????? Smart apps creator. ????? ????? ???????? ?? ??? ????? ?? ????? ????? ???????? ???? ?????? ADDIE. ?????? ??? ??????? ????? ADDIE (??????? ???????? ???????? ???????? ????????). ?? ????? ????? ???????? ????????? ???? ????. ??? ??? ????? ????? ???? ???? ?????? ??? ???? ?????? ?? ??????? ????? ???????. ??????? ?????? ?????? ?????? ??????? ?? ????? ?????? ???????? ?????? ???? ?????? ????? ???? ???????? ????? ?????? ??? ??????? ?????? ??????? ???? ?????? ?????? ????????? ??????? ?????? ??? ??????. ???? ????? ??? ????? ??? ?? ????? ??????? ???????? Smart apps creator ???? Spline ???? ???? ??????? ???? ?????????? ?? ????? ?????? ??????? ???? ???? ?? ????? ???? ?????? (92%) ?????? ???? ????? ?????? ???? ??????? (76%) ?????? ????? ?????? ???? ????? ?????? (89%) ?????? ???? ????? ??? ????? ?????? (91%) ?????? ???? ????.????? ??????: ?????? ?????? Smart apps creator ???? Spline